1982
DOI: 10.1113/jphysiol.1982.sp014153
|View full text |Cite
|
Sign up to set email alerts
|

Ions and energy metabolism in duck salt‐gland: possible role of furosemide‐sensitive co‐transport of sodium and chloride

Abstract: SUMMARY1. The effects of methacholine on net ionic movements and energy metabolism of the avian salt-gland have been studied, using slices of glands taken from salt-adapted Pekin ducks. The slices were equilibrated with media and drugs for 120 min at 1 0C before the experimental incubation at 38 'C.2. During incubation at 38 'C the slices accumulated K+ and lost Na+ and Cl-. In the presence of methacholine, they retained more Na+ and Cl-and accumulated less K+, the maximal effects being given by 05-1 0 mM-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…It is unclear why an increase in RNA synthesis could not be detected under in vitro conditions, since previous studies indicate that total RNA content of the salt gland increases following saIt stress (Holmes and Stewart, 1968). Although some cellular metabolic activities of the salt gland may require continuous cholinergic stimulation (Stewart et al, 1979;Stewart and Sen, 1981;Ernst and Van Rossum, 1982), we found no effect by cholinergic agonists on in uitro RNA synthetic rates in either nonstressed or stressed salt-gland slices (data not shown). In contrast to the in vitro studies, however, the in vivo rates found in the present study are consistent with earlier observations and appear to reflect true biosynthetic events.…”
Section: Discussioncontrasting
confidence: 70%
“…It is unclear why an increase in RNA synthesis could not be detected under in vitro conditions, since previous studies indicate that total RNA content of the salt gland increases following saIt stress (Holmes and Stewart, 1968). Although some cellular metabolic activities of the salt gland may require continuous cholinergic stimulation (Stewart et al, 1979;Stewart and Sen, 1981;Ernst and Van Rossum, 1982), we found no effect by cholinergic agonists on in uitro RNA synthetic rates in either nonstressed or stressed salt-gland slices (data not shown). In contrast to the in vitro studies, however, the in vivo rates found in the present study are consistent with earlier observations and appear to reflect true biosynthetic events.…”
Section: Discussioncontrasting
confidence: 70%
“…3). A similar delay of net K+ uptake is also seen in rat liver slices (Judah & McLean, 1962;Elshove & van Rossum, 1963;van Rossum, 1970b) but not in rat renal cortex, rat lung or avian salt gland (Ernst & van Rossum, 1982;Russo et al 1985; M. F. Mariani & G. D. V. van Rossum, unpublished). Intracellular Na+ initially followed a similar course to water and Cl-but, unlike the latter, continued to decline after 30 min.…”
Section: Rabbit Liver Slices Net Movements Of Ions and Watermentioning
confidence: 64%
“…The concentration mechanism employed by chelonian salt glands is unknown. In birds there is evidence of transepithelial Cl~ secretion (Ernst & van Rossum, 1982), although the initial fluid at the blind end of the salt gland tubules appears to be isotonic with blood (Marshall etal. 1985), and it is suggested that the fluid is concentrated, as it passes along the duct, by water absorption across the duct wall under the influence of a standing osmotic gradient, and that further ionic modifications in the fluid composition are brought about by ion pumps (Ellis et al 1977;Marshall et al 1985).…”
Section: Tear Formationmentioning
confidence: 99%